Effect on climatic factor towards the population of rhinoceros beetle in oil palm plantation: a review / Nurul Shuhada Subri - Subri, Nurul Shuhada (Faculty of Plantation and Agrotechnology, 2017)
Rhinoceros beetle was a major pest on oil palm crops which comes from family Scarabaeidae. The objectives of the study to made in order to evaluate the population of rhinoceros beetle that causing damage which affected by climatic factor such as rainfall, relative humidity and temperature. In fact, once rhinoceros beetles attack on oil palm, about 40 percent to 92 percent of damage can cause losses in oil palm production. The present results confirm the population of rhinoceros beetles towards oil palm for three largest oil palm production countries which are Indonesia, Malaysia and Nigeria. In Indonesia show that about 288, Malaysia was 200 and Nigeria was 300 of rhinoceros beetle population per acre. Even though average rainfall in Indonesia (287 mm) was lower than Malaysia (2309mm) but in term of population, Indonesia was higher than Malaysia it was happened because of it related to relative humidity factor which are Indonesia (85%) was higher than Malaysia (77%). Through the comparison between Indonesia and Nigeria, the population was higher than Indonesia because it related to average rainfall factor when the average rainfall in Nigeria (1800mm) was higher than Indonesia (287mm). Beetles are most active during rainy period. Thus, the temperature factor it showed the population of rhinoceros beetle in Nigeria (30⁰C) and Indonesia (27⁰C) was higher than Malaysia (24⁰C) because they are best suited in temperature around 27⁰C to 29⁰C. In conclusion, the population of rhinoceros beetle is really affected by temperature factor for the three countries which are Indonesia, Malaysia and Nigeria. Through this evaluation the management practices can be adopted based on appropriate time in order to control the population of rhinoceros beetle.